2018
DOI: 10.26434/chemrxiv.7122089.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benchmarking Computational Alchemy for Carbide, Nitride, and Oxide Catalysts

Abstract: <p>Kohn-Sham density functional theory (DFT)-based searches for hypothetical catalysts are too computationally demanding for wide searches through diverse materials space. Our group has been critically evaluating the performance of an alternative computational method called computational alchemy. An advantage with this method is that it effectively brings no computational cost once a single DFT reference calculation is made. Extending from our 2017 publication in <i>J. Phys. Chem. Lett </i>(D… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 6 publications
3
13
0
Order By: Relevance
“…Conversely, this argument explains why ∆Z is the most important feature. It was also reported in our previous work [29,30] (and shown in Figure 1) that for a larger nuclear charge perturbation, the errors are larger, regardless of the location of the change. Thus, for the part of the dataset where the change is large (ie.…”
Section: Modelsupporting
confidence: 81%
See 2 more Smart Citations
“…Conversely, this argument explains why ∆Z is the most important feature. It was also reported in our previous work [29,30] (and shown in Figure 1) that for a larger nuclear charge perturbation, the errors are larger, regardless of the location of the change. Thus, for the part of the dataset where the change is large (ie.…”
Section: Modelsupporting
confidence: 81%
“…In our previous work [29,30], we showed that the accuracy of APDFT approximations requires that N T and ∆Z should both be small. In general, this means that APDFT approximations are most accurate when the hypothetical system does not have more than a single atom transmuted by more than one group of the periodic Here the binomial notation is used for showing the combinatorics of one transmuted atom in any of the eight atomic sites in the top two layers of this system, and the prefactor of 2 refers to the fact that transmutations could be either +1 (into Au) or -1 (into Ir).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our previous work, 29,30 we showed that the accuracy of APDFT approximations requires that N T and ΔZ should both be small.…”
mentioning
confidence: 95%
“…[24][25][26] APDFT has also been tested for predicting material properties of bulk transition metals, 27 semiconductor band gaps and stability, 26,28 and molecular adsorptions on nanoparticles and extended surfaces. 22,24,29,30 The majority of these applications have used the Taylor series expression truncated to first order, which thus assigns a linear relationship between the energy perturbation and the alchemical derivatives of the reference shown in Equation 2.…”
mentioning
confidence: 99%